Extreme value theory: An application to the Peruvian stock market returns - Gabriel Rodríguez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
Using daily observations of the index and stock market returns for the Peruvian case from January 3, 1990 to May 31, 2013, this paper models the distribution of daily loss probability, estimates maximum quantiles and tail probabilities of this distribution, and models the extremes through a maximum threshold. This is used to obtain the better measurements of the Value at Risk (VaR) and the Expected Short-Fall (ES) at 95% and 99%. One of the results on calculating the maximum annual block of the negative stock market returns is the observation that the largest negative stock market return (daily) is 12.44% in 2011. The shape parameter is equal to -0.020 and 0.268 for the annual and quarterly block, respectively. Then, in the first case we have that the non-degenerate distribution function is Gumbel-type. In the other case, we have a thick-tailed distribution (Fréchet). Estimated values of the VaR and the ES are higher using the Generalized Pareto Distribution (GPD) in comparison with the Normal distribution and the differences at 99.0% are notable. Finally, the non-parametric estimation of the Hill tail-index and the quantile for negative stock market returns shows quite instability.
Keywords: C22; C58; G32; 330; extreme value theory; value-at-risk (VaR); expected short-fall (ES); generalized Pareto distribution (GPD); Gumbel distribution; exponential distribution; Fréchet distribution; extreme loss; Peruvian stock market